2017
DOI: 10.3847/1538-4357/aa876f
|View full text |Cite
|
Sign up to set email alerts
|

Twelve Years of Spectroscopic Monitoring in the Galactic Center: The Closest Look at S-stars near the Black Hole

Abstract: We study the young S-stars within a distance of 0.04 pc from the supermassive black hole in the center of our Galaxy. Given how inhospitable the region is for star formation, their presence is more puzzling the younger we estimate their ages. In this study, we analyze the result of 12 years of high-resolution spectroscopy within the central arcsecond of the Galactic Center (GC). By co-adding between 55 and 105 hr of spectra we have obtained high signal-to-noise H- and K-band spectra of eight stars orbiting the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
162
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(173 citation statements)
references
References 69 publications
9
162
1
1
Order By: Relevance
“…In the published literature, 24 RV measurements, beginning in the year 2000, have been reported from WMKO (Ghez et al 2003(Ghez et al , 2005(Ghez et al , 2008Boehle et al 2016) and 40 measurements, beginning in 2003, have been reported from the VLT (Eisenhauer et al 2005;Gillessen et al 2009aGillessen et al , 2017Habibi et al 2017). Many of the RV measurements are based on multiple nights of observations.…”
Section: Previously Reported Datamentioning
confidence: 99%
See 2 more Smart Citations
“…In the published literature, 24 RV measurements, beginning in the year 2000, have been reported from WMKO (Ghez et al 2003(Ghez et al , 2005(Ghez et al , 2008Boehle et al 2016) and 40 measurements, beginning in 2003, have been reported from the VLT (Eisenhauer et al 2005;Gillessen et al 2009aGillessen et al , 2017Habibi et al 2017). Many of the RV measurements are based on multiple nights of observations.…”
Section: Previously Reported Datamentioning
confidence: 99%
“…This limit depends on the total mass M tot used in Equation (5). In this work, two extreme values for M tot are considered: (i) a low value of M tot = 10 M e (Habibi et al 2017 reported the mass of S0-2 as 13.6 1.8…”
Section: Is S0-2 a Binary?mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Morris & Serabyn (1996) suggested that the constant inflow of gas might trigger star formation that could play a role when accretion processes are investigated. Followed by this, the detection of young stars in the Galactic Center, mostly O/B and Wolf Rayet WR stars, indicate a recent star-forming epoch (Eisenhauer et al 2005;Habibi et al 2017). Ghez et al (2003) formulated the 'paradox of youth' where the authors reflect the contrary situation.…”
Section: Introductionmentioning
confidence: 97%
“…Of a particular interest is the inner cluster within the projected radius of ∼1 ′′ ≃ 0.04 pc, which consists of ∼30 mostly B-type bright stars -the so-called S cluster (Eckart & Genzel 1996, 1997Ghez et al 1998;Gillessen et al 2009Gillessen et al , 2017Habibi et al 2017). These stars have nearly isotropic distribution of elliptical orbits with considerable eccentricities and pericenter distances of ∼1,500 Schwarzschild radii and orbital velocities at the periapse of several thousand kilometers per second.…”
Section: Introductionmentioning
confidence: 99%